Smart Design of Nanostructures for Boosting Tumor Immunogenicity in Cancer Immunotherapy - Bohan Yin; Wai-Ki Wong; Yip-Ming Ng; Mo Yang; Franco King-Chi Leung; Dexter Siu-Hong Wong (MDPI AG, 2023)
Although tumor immunotherapy has emerged as a promising therapeutic method for oncology, it encounters several limitations, especially concerning low response rates and potential off-targets that elicit side effects. Furthermore, tumor immunogenicity is the critical factor that predicts the success rate of immunotherapy, which can be boosted by the application of nanotechnology. Herein, we introduce the current approach of cancer immunotherapy and its challenges and the general methods to enhance tumor immunogenicity. Importantly, this review highlights the integration of anticancer chemo/immuno-based drugs with multifunctional nanomedicines that possess imaging modality to determine tumor location and can respond to stimuli, such as light, pH, magnetic field, or metabolic changes, to trigger chemotherapy, phototherapy, radiotherapy, or catalytic therapy to upregulate tumor immunogenicity. This promotion rouses immunological memory, such as enhanced immunogenic cell death, promoted maturation of dendritic cells, and activation of tumor-specific T cells against cancer. Finally, we express the related challenges and personal perspectives of bioengineered nanomaterials for future cancer immunotherapy.